2014
DOI: 10.1115/1.4027061
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Model to Describe the Regional Interlamellar Shear of the Annulus Fibrosus

Abstract: A Computational Model to Describe the Regional Interlamellar Shear of the Annulus FibrosusInterlamellar shear may play an important role in the homeostasis and degeneration of the intervertebral disk. Accurately modeling the shear behavior of the interlamellar compartment would enhance the study of its mechanobiology. In this study, physical experiments were utilized to describe interlamellar shear and define a constitutive model, which was implemented into a finite element analysis. Ovine annulus fibrosus (AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Furthermore, changes in both ITL and lamellar strain decreased with greater applied load. These observed differences are qualitatively consistent with trends we found in a previous study, 33 in which a nonlinear constitutive model parameters fit to surface strain measurements yielded a interlamellar shear modulus that was roughly half the lamellar shear modulus, both of which increased with higher applied strain (strain stiffening). However, in contrast to previous studies using lower applied shear strains, 47 our averaged ITL and lamellar shear strain was not equal to the applied strain; this could be an indication of matrix damage, likely in the ITL compartment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, changes in both ITL and lamellar strain decreased with greater applied load. These observed differences are qualitatively consistent with trends we found in a previous study, 33 in which a nonlinear constitutive model parameters fit to surface strain measurements yielded a interlamellar shear modulus that was roughly half the lamellar shear modulus, both of which increased with higher applied strain (strain stiffening). However, in contrast to previous studies using lower applied shear strains, 47 our averaged ITL and lamellar shear strain was not equal to the applied strain; this could be an indication of matrix damage, likely in the ITL compartment.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have suggested that the ITL compartment contributes little to AF mechanics in radial tension. 23,45,46 Instead, it has been postulated that the ITL may play a greater role in maintaining annular integrity during shear loading, 32,33 as supported by the absence of sliding between lamellae due to fibrous interlamellar connectivity. 47 At high deformations, however, the ability for interlamellar sliding to occur suggests complexity in the load sharing between the ITL and lamellar matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Therefore, extending the existing theoretical framework would be helpful to describe the ILM shearing interaction. [56][57][58] Structural damage to the lamellae, mainly as a consequence of degeneration, might increase ILM shear stress and damage propagation.…”
Section: Inter-lamellar Matrix Micromechanical Propertiesmentioning
confidence: 99%
“…The ILM shear strength has been found to increase with lamella thickness [22], and deform by up to 10 mm, having a mean (SD) peak shear strength of 0.03 (0.05) MPa during delamination [23]. Significantly different shear stress and strain distributions, with a trend of being greater in the lamella than across the ILM, were found in disc mechanical modelling when inter-lamellar connectivity was considered [24,25]. Also higher strain was reported in the ILM compared to the intra-lamellar region in bovine discs [26].…”
Section: Introductionmentioning
confidence: 97%